Sand Dunes’ Characteristics in Al Nofoud Al Kabeer Province -Northern Hail- Study on Empirical Geomorphology Using Integration between (RS), Remote Sensing and (GIS) - Awawdeh, Mohsen Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: The research aimed to monitor, observe, and model sand dunes in the Al Nofoud Al Kabeer region of Hail. It explored attributes, variations, shapes, formations, and impacts of sand dunes. The study also examined temporal changes, assessed risks, and proposed mitigation strategies. Methods: The study used remote sensing and geographic information systems. Satellite imagery from 1988 (Landsat 4, TM sensor) and 2022 (Landsat 8, OLI sensor) was employed. A supervised classification with ERDAS Imagine (V.16.7) was employed. Geological, topographic, and hydrological maps analyzed geomorphological characteristics and sand dune attributes. Results: The results showed that sand dunes covered 12,548.87 sq. km (98.61% of land cover), agricultural land covered 167.41 sq. km (1.32%), and urban areas covered 9.43 sq. km (0.07%). Sand dune types included longitudinal, dome-shaped, and sand sheets, covering 3,309.49, 1,766.26, and 259.91 sq. km respectively. Dunes mainly moved east to west, with the highest growth rates in the north and northwest due to wind. The dune movement affected 46.23% of agricultural lands in northern, eastern, and western directions. Additionally, 42% of urban areas experienced sand encroachment. Conclusions: Visuals revealed diverse sand dunes and their movement direction, negatively impacting agriculture and urban areas. Geomorphology, remote sensing techniques, and morphometry were key in understanding Al Nofoud Al Kabeer's landscape.